2020
DOI: 10.14710/jil.18.1.162-170
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Informal Actors Of Plastic Waste Recycling In Semarang City

Abstract: ABSTRAKKegiatan daur ulang sampah di Kota Semarang dapat dilakukan dengan cukup baik berkat campur tangan dari sektor informal. Sayangnya, kegiatan pengelolaan sampah formal tidak mempertimbangkan nilai pemulihan sampah. Penelitian ini bertujuan untuk mengidentifikasi aliran sampah plastik di sektor informal di Kota Semarang. Peneliti menggunakan wawancara mendalam untuk mengumpulkan data. Ada 46 agen daur ulang, termasuk lima (5) pemulung, 17 pengepul 20 perusahaan skala kecil, tiga (3) perusahaan skala besar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Sektor informal dalam pengelolaan sampah meliputi kegiatan daur ulang sampah bernilai ekonomis, yang biasa dilakukan oleh pemulung keliling, ataupun pembeli barang bekas keliling (Samadikun et al, 2020;Satori et al, 2020). Selain itu terdapat pengepul yang berperan untuk melakukan pemilahan sampah berdasarkan jenis material sampah.…”
Section: E Sektor Informalunclassified
“…Sektor informal dalam pengelolaan sampah meliputi kegiatan daur ulang sampah bernilai ekonomis, yang biasa dilakukan oleh pemulung keliling, ataupun pembeli barang bekas keliling (Samadikun et al, 2020;Satori et al, 2020). Selain itu terdapat pengepul yang berperan untuk melakukan pemilahan sampah berdasarkan jenis material sampah.…”
Section: E Sektor Informalunclassified
“…The World Bank has reported that approximately 760,000 tons per day of plastic waste is generated in Asia, which is predicted to increase up to 1.8 million tons or approximately 5.2 million m 3 per day by 2025 . Typically, plastic waste is treated by burying it in the ground (landfill) or by burning it (incineration) . However, both these methods have a negative impact on the environment owing to air, soil, and water pollution. , …”
Section: Introductionmentioning
confidence: 99%
“…6 Typically, plastic waste is treated by burying it in the ground (landfill) or by burning it (incineration). 7 However, both these methods have a negative impact on the environment owing to air, soil, and water pollution. 8,9 Expanded polystyrene (EPS) is a plastic waste containing harmful substances, such as benzene and styrene.…”
Section: Introductionmentioning
confidence: 99%